Death caused by negligent medical care: Reconsidering the role of gross negligence manslaughter in the aftermath of Bawa-Garba. (December 2021) - Samanta, Ash; Samanta, Jo
Gross negligence manslaughter is a well-established common law offence in English jurisdiction. Nevertheless, it remains a troubled area of law. Academic commentators, as well as the Law Commission, have frequently called for reform. We explore this offence through the prism of medical manslaughter and argue that the offence is insufficiently nuanced in certain situations of death caused by gross negligence. This applies particularly to complex professional circumstances where a coalescence of inter-linking factors may converge with disastrous results for the parties concerned. Using the clinical care model as an exemplar, we argue that relentless focus on the offender can result in a disproportionately high level of blame being foisted on an individual. On the basis of decision theory, we suggest that insufficient regard may be given to confounding contextual matters. Failure to address underlying systemic factors may impede wider patient safety initiatives such as professional medical candour and strategies designed for institutional improvements directed at broader societal benefit. We offer an alternative approach based upon principles of fair attribution of blame and transparency. A new statutory offence is suggested for a fault-based standard that is set by law that gives greater prominence to contextual matters. We argue for wider disposal options that include ancillary court orders for rectification of systems failures and more proactive engagement of the coronial process.